Comparison of the efficacy of 3% hypertonic saline and 20% mannitol in reducing intracranial pressure in patients with traumatic brain injury - Prakash, Anand; Kumar, Vikas; Kumar, Deepak; Ali, Manjar; Ansari, M. Habibullah (International Journal of Research in Medical Sciences, 2024)
Background: Objective of the study was to compare the effects of 3% hypertonic saline (HTS) solution and 20% mannitol (MTL) solution on intracranial hypertension. Methods: The prospective study subjects consisted of 60 patients with traumatic brain injury admitted to the Department of Neurosurgery, RIMS, Ranchi between March 2020 to February 2023. The subjects fulfilling the inclusion criteria were selected and divided into two groups: group A (n=30): treated with 3% HTS, and group B (n=30): treated with 20% MTL. Results: All the findings were noted on Microsoft excel sheet and data were analyzed using the statistical package for the social sciences (SPSS) 21.0 package. Quantitative data were analyzed using student’s t-test (paired and unpaired) and categorical data were analyzed by the test of proportion, Chi-square, and Fisher’s exact test. Conclusions: Both 3% HTS and MTL can effectively reduce intracranial pressure, but 3% HTS has a more sustained effect on intracranial pressure and can effectively increase cerebral perfusion pressure.